2014
DOI: 10.1128/mbio.00946-13
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Segregation of Virulence Gene Expression during Acute Enteric Infection with Salmonella enterica serovar Typhimurium

Abstract: To establish a replicative niche during its infectious cycle between the intestinal lumen and tissue, the enteric pathogen Salmonella enterica serovar Typhimurium requires numerous virulence genes, including genes for two type III secretion systems (T3SS) and their cognate effectors. To better understand the host-pathogen relationship, including early infection dynamics and induction kinetics of the bacterial virulence program in the context of a natural host, we monitored the subcellular localization and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 66 publications
8
97
0
Order By: Relevance
“…Instead, when Salmonella is grown in minimal media, the expression of ssrAB and thus the SPI-2 genes is self-regulated by SsrA/B as well as by other regulators, such as the two-component systems OmpR/ EnvZ and PhoP/Q and the MarR-like regulator SlyA (32)(33)(34)(35)(36)(37)(38). Therefore, in response to distinct growth conditions, at least two different pathways induce the expression of the ssrAB genes in vitro, which may be consistent with the fact that the SPI-2 genes can be expressed in different compartments inside Salmonella hosts (18).…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Instead, when Salmonella is grown in minimal media, the expression of ssrAB and thus the SPI-2 genes is self-regulated by SsrA/B as well as by other regulators, such as the two-component systems OmpR/ EnvZ and PhoP/Q and the MarR-like regulator SlyA (32)(33)(34)(35)(36)(37)(38). Therefore, in response to distinct growth conditions, at least two different pathways induce the expression of the ssrAB genes in vitro, which may be consistent with the fact that the SPI-2 genes can be expressed in different compartments inside Salmonella hosts (18).…”
supporting
confidence: 49%
“…SPI-2 genes also induce a nonproliferative intracellular lifestyle by restraining growth inside phagocytes and nonphagocytic cells and contribute to the development of intestinal inflammatory and diarrheal disease, as they enhance Salmonella's transepithelial passage, as well as foster growth inside phagocytes present in the lamina propria (6)(7)(8)(9)(10)(11)(12). In agreement with their pathogenicity roles, SPI-1 genes are expressed when bacteria are in the intestinal lumen or associated with the epithelium or with extruding enterocytes, as well as in a subpopulation of bacteria hyperreplicating in the cytosol of epithelial cells, whereas SPI-2 genes are expressed when bacteria are inside macrophages and also when they are in the intestinal lumen prior to penetrating the intestine, as well as in the lamina propria and in the underlying mucosa (13)(14)(15)(16)(17)(18). In vitro, the SPI-1 and SPI-2 genes are expressed during early and late stationary phase, respectively, when Salmonella is grown in nutrient-rich media, such as Luria-Bertani (LB) medium (19)(20)(21)(22).…”
mentioning
confidence: 61%
“…In vivo it is likely that macrophages will encounter bacteria with various transcriptional profiles, often at low MOIs. For example, SPI1-induced bacteria are released from infected epithelial cells in vivo (21,22). Further study is required to determine what role the number of intracellular bacteria plays in the induction of pyroptosis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Since the internalization of Salmonella into phagocytic cells does not require T3SS1, studies of Salmonella infection in macrophages generally are done with bacteria grown to stationary phase. However, SPI1-induced Salmonella Typhimurium is re-leased from epithelial cells, suggesting that SPI1-induced bacteria can be encountered by macrophages in vivo (21,22).…”
mentioning
confidence: 99%
“…In S. enterica ser. Typhimurim, the subcellular localization and temporal expression of type III secretion systems 1 and 2 were analyzed using fluorescent reporters and microscopy during acute enteric infection in a bovine model (Laughlin et al, 2014). Interestingly, the authors revealed differential expression of the different virulence genes depending on the anatomical location of Salmonella in the model, as well as the changes in its spatiotemporal expression during infection.…”
Section: Basic Understanding Of Food Bacteria Functionmentioning
confidence: 99%